The UK HeartSpare Study (Stage IB): Randomised comparison of a voluntary breath-hold technique and prone radiotherapy after breast conserving surgery. Issue 1 (January 2015) - Bartlett, Frederick R.; Colgan, Ruth M.; Donovan, Ellen M.; McNair, Helen A.; Carr, Karen; Evans, Philip M.; Griffin, Clare; Locke, Imogen; Haviland, Joanne S.; Yarnold, John R.; Kirby, Anna M.
Abstract: Purpose: To compare mean heart and left anterior descending coronary artery (LAD) doses (NTDmean ) and positional reproducibility in larger-breasted women receiving left breast radiotherapy using supine voluntary deep-inspiratory breath-hold (VBH) and free-breathing prone techniques. Materials and methods: Following surgery for early breast cancer, patients with estimated breast volumes >750 cm 3 underwent planning-CT scans in supine VBH and free-breathing prone positions. Radiotherapy treatment plans were prepared, and mean heart and LAD doses were calculated. Patients were randomised to receive one technique for fractions 1–7, before switching techniques for fractions 8–15 (40 Gy/15 fractions total). Daily electronic portal imaging and alternate-day cone-beam CT (CBCT) imaging were performed. The primary endpoint was the difference in mean LAD NTDmean between techniques. Population systematic ( Σ ) and random errors ( σ ) were estimated. Within-patient comparisons between techniques used Wilcoxon signed-rank tests. Results: 34 patients were recruited, with complete dosimetric data available for 28. Mean heart and LAD NTDmean doses for VBH and prone treatments respectively were 0.4 and 0.7 ( p < 0.001) and 2.9 and 7.8 ( p < 0.001). Clip-based CBCT errors for VBH and prone respectively were ⩽3.0 mm and ⩽6.5 mm ( Σ ) and ⩽3.5 mm and ⩽5.4 mm ( σ ). Conclusions: In larger-breasted women, supine VBH provided superior cardiac sparing and reproducibility than a free-breathing prone position.